Case Report and Literature Review: Catastrophic Embolism Following Cosmetic Injection of Autologous Fat in the Face - Liu, Chunyu; Cai, Zhaolun; Zhang, Lingli; Zhou, Muke; He, Li (Frontiers in Medicine, 2021)
Injection of autologous fat into the face is a commonly performed procedure in plastic surgery. However, it can lead to rare but devastating complications due to fat embolism. Here, we presented two cases of cerebral infarction and/or sudden vision loss after cosmetic injections of autologous fat into the face. These two women underwent injection into the temporal and frontal areas, respectively. In case 1, the patient underwent decompressive craniectomy as her condition deteriorated continuously and died. In case 2, the patient’s vision had not improved at the 3-month follow-up visit. Imaging examinations showed occlusion of the right external carotid artery in case 1, and multiple retinal arterioles were segmentally occluded in case 2. We also screened relevant studies via a systematic search of PubMed (last updated on May 9, 2020) and performed a narrative review due to the significant heterogeneity between studies. To prevent this catastrophic event, autologous fat injection should be performed carefully. If embolization does occur, early diagnosis and timely treatment may help improve functional outcomes.